Pattern of Antibiotic in Community-Acquired Pneumonia (CAP) Comparison in Type A and B Hospital - Ika Puspita Sari; Titik Nuryastuti; Rizka Humardewayanti Asdie; Anton Pratama; Endang Estriningsih (Faculty of Pharmacy, Universitas Gadjah Mada)
Pneumonia is a threat to all States. CAP treatment in hospitals typically uses empirical antibiotic therapy with IDSA/ATS guidelines. This research aimed to compare empirical antibiotic therapy of CAP patients in types A and B hospital and to analyze the variations that occur and compare the outcome of the therapy. The research was conducted retrospectively by collecting data from the medical records of patients diagnosed with CAP. The inclusion criteria in this research were male and female adult patients aged ≥18 years who had complete medical record data. Patients who underwent inpatient care in the in-patient wards (non ICU) of type A and B hospital received empirical antibiotic therapy. Data from type A hospital (RS A) were taken within the period of January 2014-December 2016, while data from type B hospital (RS B) were taken in January 2013-December 2016. The number of patients with CAP in hospital A is 72, whereas in hospital B, it is 34. Patients with malignancy and immunocompromise were excluded from this research. In this research, germs found in hospital A were mapped, while no gynecologic examination/culture was performed in hospital B. The outcome of the treatment was an improvement in response 5-7 days after empirical antibiotics was given, as reported by a physician and/or by an improvement in the x-ray thorax results. Patient demographic data and antibiotic therapy pattern were analyzed descriptively. Outcome of patient therapy was analyzed using Chi square statistics with 95% confidence level.The results showed that empirical antibiotic therapy in CAP patients in type A hospital were largely based on IDSA/ATS guidelines, whereas in it is the opposite for type B hospital. Outcomes of patient therapy in A and B hospitals showed patient improvement of about 76%. In type A hospital, the cause of CAP is largely negativeGram bacteria which are still sensitive to cephalosporin/carbapenem (cefpirom, ceftasidim, cefepim, and imipenem) and aminogicosida (amikacin, netilmisin, and tobramisin).